From stories to loyalty - How does digital narratives on Instagram influence consumer engagement with premium clothing brands in Scandinavia? - Sjöberg Nehlin,Viktor (2025)
This study investigates how premium clothing brands use digital narratives on Instagram to foster meaningful consumer engagement, explicitly focusing on Scandinavian cultural contexts. The study used a combination of survey data and expert interviews to examine how branded content could mediate consumers' emotional and cognitive responses based on the structures of Instagram. The findings indicate that Scandinavian consumers value authenticity, sustainability, and cultural relevance over surface-level engagement metrics such as likes or views. The study highlights the importance of influencer-brand alignment and culturally resonant storytelling by drawing on Horton and Wohl’s (1956) theory of parasocial interaction and Abidin’s (2016) concept of visibility labour. Younger users responded more strongly to creative, aesthetic-driven content, while broader engagement remained limited. The study concludes that premium brands operating in this region must shift focus from broad reach to trust-based, narrative-driven strategies that reflect shared cultural values and foster long-term loyalty
Keywords: Premium clothing branding: Consumer engagement; Brand loyalty; Visual communication & Social media strategy